Modal Test and Analysis of the Engine,Gearbox and Frame of a Light Truck - Wang Junyuan; Li Weiwei; Ma Weijin; Zhang Jiping (Jixie chuandong)
The modal of engine,gearbox and frame are tested by the method of hammer excitation,and the modal parameters are obtained. Through interception the vibration signals when the empty light truck on washboard road and obstacles road,the modal test analysis of the vibration signal is carried out,the modal parameters of different stages of the light truck in the working environment are obtained. Finally,the test results are summarized and analyzed,several sensitive modal frequencies are found. Those found would provide theory and technical support for further study on dynamic analysis to estimate the basic reason of the damaging of the engine,gearbox and the frame.